The Financial Culture in the Lima Este Micro-Enterprises, year 2017 - Vicente Armas, Edgar (2019)
Lima East to 2014 has 172 481, micro businesses (Cieneguilla 1 503, Chaclacayo 3 250, San Luis 9 144, Lurigancho 10 793, El Agustino 11 281, La Molina 16 500, Santa Anita 18 973, Ate 41 874 and San Juan de Lurigancho 59 163), which represents 20% of the total; it concentrates 29.9% of the total population of Metropolitan Lima. According to the INEI (2015) one of the main factors that limit the growth of companies is the lack of accessibility to the financing of financial products offered by financial institutions. By the way, the results of the survey conducted in the districts that make up the East Lima in November (2017), show us the following results: 77.7% of the Micro Enterprises of Lima Este are located in the districts of San Juan de Lurigancho, Ate, La Molina and Agustino; 83.9% are dedicated to the activity of Commerce and Services, 71.2% are subject to loans, 71.8% know their indebtedness and 92% require loans for the financing of working capital and the purchase of fixed assets.